Joint association of physical activity and the geriatric nutritional risk index with survival outcomes among cancer survivors in the United States: a population-based cohort study - Wei, Jing; Zeng, Qingyue; Liu, Ming (Frontiers in Nutrition, 2024)
IntroductionThe relationship between physical activity (PA) and nutritional status on the prognosis of cancer survivors remains underexplored. We aimed to investigate the combined effects of PA and Geriatric Nutritional Risk Index (GNRI) on prognostic assessment of survival outcomes in US cancer survivors.Methods2,619 subjects were screened from the National Health and Nutrition Examination Survey (NHANES) database from 1999 to 2018. The self-reported Global Physical Activity Questionnaire (GPAQ) for PA assessment, and the GNRI for nutritional status assessment. Kaplan–Meier (K-M) curves and Cox proportional risk models were used to evaluate the effect of PA combined with GNRI on the prognostic outcomes of death in cancer survivors.ResultsThe sufficient PA (≥600 MET min/week) combined with High-GNRI (>98) subgroups significantly reduced the risk of all-cause mortality (HR: 0.56; 95% CI, 0.35–0.90) and cancer-related mortality (HR: 0.24; 95% CI, 0.12–0.50) compared to other subgroups. Subgroup analyses indicated that the combination of sufficient PA and High-GNRI was associated with a significantly reduced all-cause and cancer-related mortality among specific groups-including individuals of female, patients with non-obesity-related cancers, and those with higher educational attainment. After excluding participants who died within the first 12 months of follow-up, sensitivity analyses confirmed the robustness of the association between PA and GNRI in predicting prognostic outcomes among cancer survivors.ConclusionOur study shows that among U.S. cancer survivors, sufficient PA combined with High-GNRI is linked to reduced mortality. These findings emphasize the benefits of PA and nutritional status in improving prognosis and support the need for further studies to develop targeted interventions.